2018
DOI: 10.1111/jonm.12624
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner integration: Qualitative experiences of the change management process

Abstract: The results of this study highlight the importance of management and leadership in the promotion of advanced nursing skills and experience to better meet patient outcomes. The findings reinforce the potential of nurse practitioners to deliver patient centred, timely and efficient health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…In a related vein, perspectives regarding these professionals’ scope of practice have previously been identified, whether related to the interpretation of this scope by physicians [17, 27] or registered nurses [17, 19] or to PHCNPs’ beliefs that their scope of practice is unduly limited [14, 16, 45]. The tension between the biomedical and nursing paradigms has been noted in some other investigations [13, 14, 19, 46]. Some other studies also have identified a lack of congruence between the reality of PHCNPs’ roles and the structures in which their practice is situated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a related vein, perspectives regarding these professionals’ scope of practice have previously been identified, whether related to the interpretation of this scope by physicians [17, 27] or registered nurses [17, 19] or to PHCNPs’ beliefs that their scope of practice is unduly limited [14, 16, 45]. The tension between the biomedical and nursing paradigms has been noted in some other investigations [13, 14, 19, 46]. Some other studies also have identified a lack of congruence between the reality of PHCNPs’ roles and the structures in which their practice is situated.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors that have been identified include: reimbursement policies [7, 1315]; scope of practice clarity [7, 14, 16]; role definition, comprehension and recognition [7, 13, 14, 1720]; integration process into primary care settings [21, 22]; organisational/administrative support [7, 13, 14, 18, 20, 23, 24]; work climate [25]; team functioning in general [26] and collaboration between APNs and physicians [13, 17, 19, 2729] and with registered nurses and other professionals [16, 17, 19]. Studies have demonstrated the positive impact associated with adopting an systematic process to implementing the PHCNP role [19, 21]. In a related vein, others have noted the importance of considering multiple levels (e.g., organisational, health care system) in better understanding the elements needed for an optimal implementation [3, 16, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurse practitioner role has been associated with extensive research to date primarily describing work practices. Integration relates to the normalization of the nurse practitioner becoming embedded in‐service delivery and differs from nurse practitioner roles as pilot or test initiatives (Lowe et al, 2018). The integration of nurse practitioner roles depends on a structured, multilevel support system to ensure they are embedded within the service rather than an ‘add on’ (Contandriopoulos et al, 2015; Lowe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The NP role, conceived in the United States over 50 years ago, has been seen to include both leadership, by implementing quality patient care practices, and research, by investigating the outcomes of care provided (Ford, 2015; Lowe, Plummer, & Boyd, 2018; Ryder et al, 2019). Leadership outcome indicators for NPs identified by Elliott et al (2014) include research in the form of research application, evaluation and knowledge generation.…”
Section: Introductionmentioning
confidence: 99%